A study on the role of interior design in the reduction of allergen and irritant exposure among selected residential interior space-users with allergic rhinitis in Quezon City - Guiang, Gillian B. (College of Home Economics, University of the Philippines Diliman, 2018)
This research which utilized a multiple case study approach, sought to determine whether or not interior design played a role in reducing the exposure of individuals with allergic rhinitis to allergens and irritants in a bedroom space. Six females who were diagnosed with allergic rhinitis and who live Quezon City were purposively chosen as respondents. Data gathering procedures included interviews with an allergist and the respondents with allergic rhinitis, as well as observation of the respondents' bedroom space. Based on the data gathered on the allergist and the guidelines foe allergen avoidance cited in the review of related literature, the respondents' bedroom spaces were assessed in terms of whether these had allergen and/or irritant exposure contributors. The results show that interior design elements such as surface finishes and furnishings do have a bearing on the reduction of one's allergen and irritant exposure. The findings suggest that cleanability (how easy something is cleaned), and the absence of strong odor are of utmost importance for interiors with allergic persons. Frequent cleaning and laundering, and other housekeeping practices were also found to be beneficial in reducing one's exposure to allergen and/or irritant exposure especially since the most common allergen people are sensitive to is house dust mites (HDM). For future researchers who would want to delve into a similar topic, -exploring the relationship between allergic rhinitis and the interior environment -a study that seeks to determine which interior design strategy will work best for each kind of sensitization is strongly recommended.